A PRELIMINARY STUDY OF THE ANTI-CANCER EFFECT OF TANSHINONE ON HEPATIC CANCER AND ITS MECHANISM OF ACTION IN MICE - Wang, Xiujie; Yuan, Shulan; Wang, Chaojun; Huang, Renmin; Li, Yuqiong (Chinese Journal of Cancer Research, 2013)
Objective: There were some experimental researches in vitro, which showed that tanshinonoe (Tan) had cytotoxic activities against some cancer cell lines. But there was no report of anti-cancer activity of Tan in vivo. This experimental study was performed to confirm the anti-cancer activity of Tan in vivo. Methods: Hepatic carcinoma Hn hearing mice were treated with DMSO, 5-Fu, and Tan, at the end of experiment, the mice were sacrificed, tumor tissues were separated and weighed, and the tumor inhibitory rate was calculated, 3 times of the same experiments were performed. The proliferating kinetics of hepatic carcinoma H22 cells in mice was measured by bromodeoxyuridine labeling in vivo and immunohistocbemicai staining of the proliferating cell nuclear antigen (PCNA) in tumor tissues. Results: The tumor inhibitory rates of Tan were 50.0%, 38.5%, and 40.6% in 3 experiments, respectively, compared with those of the DMSO-treated control groups, the differences were significant statistically (P